2021
DOI: 10.1002/anie.202008395
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Optical Properties of Luminescent Semiconducting Nanocrystals through Hydrostatic, Anisotropic Static, and Dynamic Pressures

Abstract: Studies on the hydrostatic-pressure-dependent optical properties of av ariety of metal-halide perovskites will be discussed below.M etal-halide perovskites (MHPs), which have the general formula ABX 3 [A = Cs + ,C H 3 NH 3 + (methylammonium, MA), HC(NH 3 ) 2 2+ (formamidinium, FA), etc.; B = Pb 2+ ,S n 2+ ,e tc.; and X = Cl, Br, or I],h ave been widely studied because of their tremendous potential for use in many optoelectronic applications,i ncluding solar cells, [18][19][20][21] LEDs, [22][23][24][25][26] ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 146 publications
0
11
0
Order By: Relevance
“…The PL redshift, followed by a blueshift and the emission quenching have been observed in the hybrid and all-inorganic metal halide perovskite; however, there is no agreement about its origin. This process was ascribed to pressure-induced distortions of the band structure, underlying structural phase transitions, orbital interactions due to the octahedral tilting, amorphization, among other effects, as described in the review from Biesold et al 42 PL studies have been carried out on luminescent and nonluminescent Cs 4 PbBr 6 nanocrystals. Both compounds are structurally equivalent under ambient conditions, according to De Bastiani et al 54 The phase I to II transition was also confirmed in those samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PL redshift, followed by a blueshift and the emission quenching have been observed in the hybrid and all-inorganic metal halide perovskite; however, there is no agreement about its origin. This process was ascribed to pressure-induced distortions of the band structure, underlying structural phase transitions, orbital interactions due to the octahedral tilting, amorphization, among other effects, as described in the review from Biesold et al 42 PL studies have been carried out on luminescent and nonluminescent Cs 4 PbBr 6 nanocrystals. Both compounds are structurally equivalent under ambient conditions, according to De Bastiani et al 54 The phase I to II transition was also confirmed in those samples.…”
Section: Resultsmentioning
confidence: 99%
“…The PL redshift, followed by a blueshift and the emission quenching have been observed in the hybrid and all-inorganic metal halide perovskite; however, there is no agreement about its origin. This process was ascribed to pressure-induced distortions of the band structure, underlying structural phase transitions, orbital interactions due to the octahedral tilting, amorphization, among other effects, as described in the review from Biesold et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the laboratory interest in volumetric strain is mainly focused on compressive strain (hydrostatic strain) rather than tensile strain, perhaps because uniform volume stretching is difficult to achieve, or related research value remains to be further explored. [29,30] In terms of theoretical calculations, both Berdiyorov's and Jing's teams explored the properties of perovskite materials by hydrostatic strain. The former focused on electronic transport properties, while the latter comprehensively investigated the effects of structural, electronic, and optical properties.…”
Section: Volumetric Strain (Hydrostatic Strain)mentioning
confidence: 99%
“…[6,7] Quantum dot (QD) materials are endowed with quantum confinement effect, conducive to both the energy and charge transfer from/to the contacted perovskite absorber and therefore favorable for the performance improvement of PSCs. [8][9][10][11] With the incorporation of quantum dots (QDs), new path for energy transfer is constructed, and overlap between the excitation spectrum of perovskite and the emission spectrum of QDs is obtained, raising light absorption. [12] In addition, QDs assist in charge transfer as the mediators that form better energy-level alignment between perovskite layer and charge transporting layers (CTLs), contributing to the performance improvement of PSC devices.…”
mentioning
confidence: 99%